K2PdCl4/PPh3-catalyzed Carbon-sulfur Coupling Reaction; An Efficient and One-pot Method to Direct Synthesis of Organic Disulfides/Sulfides from Aryl Halides and Thiourea - Raeisi, Masoumeh; Mohammadi, Fariba; Soleiman-Beigi, Mohammad; Naghipour, Ali (Letters in organic chemistry, 2018)
This work describes an efficient and new catalyst for the one-pot synthesis of organic disulfides/sulfides via a palladium catalyst in the presence of PPh3 ligands for domino cross-coupling reaction of aryl halides and thiourea and then sulfur-transformation. Finally, the generated aryl thiolate converts to disulfide at normal oxidative and atmospheric conditions in DMF/water. However, thiols convert to unsymmetrical sulfides by one-pot reaction with alkyl halides in PEG/H2O.